Design, Synthesis and Antibacterial Evaluation of Hybrid Curcumin Based Pyrazole Derivatives: Life Sciences-Chemistry for New drug discovery - Anand Mohan Jha; Md. Mansoor Alam (International Journal of Life Science and Pharma Research, 2022)
Present work demonstrates synthesis and antibacterial property of new pyrazole derivatives. A series of new Curcumin based dihydropyrazoles has been synthesized with an objective to evaluate their antibacterial property. Dihydropyrazoles analogues were synthesized using Curcumin based chalcones and differently substituted phenylhydrazine derivatives. We used the previously designed Curcumin based chalconesto react with phenylhydrazine derivatives in ethanol in a catalyst free medium to afford new dihydropyrazole derivatives. Effect of substituent on reactivity was also studied. All the synthesized pyrazole analogues were characterized using proton and carbon NMR, Mass spectroscopy and IR techniques. Effect of substituent on reactivity was explained on the basis of electronic effect generated due to groups on phenyl ring. Presence of dd (double doublet) in proton NMR spectrum of Dihydropyrazoles was also explained due to presence of optically active carbon of pyrazole ring. The synthesized library was screened for their inhibitory activity against 4 different bacterial strains 1. E. Coli (ATCC 9637), 2. Pseudomonas aeruginosa (ATCC BAA-427), 3. Staphylococcus aureus (ATCC 25923) and 4. Klebsiella pneumonia (ATCC 27736). Out of all the compounds evaluated, the compounds that exhibited IC50 value greater than 50µM, were considered to be inactive. We established an important SAR based on the structure dependent inhibitory potential of screened dihydropyrazoles. Two compounds 4e and 4t having nitro and benzyl substitution respectively were showing the best inhibitory potential against Gram Positive bacterial strain Staphylococcus aureus with MIC value of 1.56 µg/ml. Compounds having Chloro and Methoxy substitution were found to be less effective against screened bacterial strains. Compounds 4a and 4b were selective towards Staphylococcus aureus species with the MIC value of 1.56 µg/ml for each. These pyrazole analogues were not showing inhibitory potential against other screened bacterial strains.